2015
DOI: 10.2500/aap.2015.36.3810
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of exercise-induced cough in schoolchildren: A pilot study

Abstract: Association between exercise-induced bronchoconstriction (EIB) and physical activity has not been investigated in a natural school environment in a general pediatric population. Our objective was to determine the prevalence of exercise-induced symptoms (cough, wheeze, chest tightness, dyspnea) and bronchospasm among schoolchildren during physical education (PE). A total of 557 schoolchildren from seven public schools were enrolled. Information regarding demographic characteristic, previously diagnosed asthma w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 0 publications
0
16
1
3
Order By: Relevance
“…The percentage of maximum FEV 1 decrease showed moderate correlation with a history of asthma, which differs from the results found by Cichalewski et al26 The methodological differences in the diagnosis of EIB can explain this discrepancy, as the present study used a bronchial provocation test on treadmill and in the study of Cichalewski et al,26 it was performed 45min after a physical education class. On the other hand, neither study identified an association between EIB and BMI.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…The percentage of maximum FEV 1 decrease showed moderate correlation with a history of asthma, which differs from the results found by Cichalewski et al26 The methodological differences in the diagnosis of EIB can explain this discrepancy, as the present study used a bronchial provocation test on treadmill and in the study of Cichalewski et al,26 it was performed 45min after a physical education class. On the other hand, neither study identified an association between EIB and BMI.…”
Section: Discussioncontrasting
confidence: 90%
“…O percentual de queda máxima VEF1 apresentou correlação moderada com histórico de asma, o que difere do resultado encontrado por Cichalewski et al 26. As diferenças metodológicas quanto ao diagnóstico do BIE podem explicar essa discrepância, visto que na presente pesquisa foi feito teste de broncoprovocação em esteira e, no estudo de Cichalewski et al .,26 foi feito 45 minutos após uma aula de educação física.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The symptom assessment however is subjective and may be biased by parental perception (Dales et al, 1997; Ioan et al, 2014). Diagnostic of the respiratory condition may benefit identification of a particular trigger such as exercise that is indeed sought by cough questionnaire studies (Suguikawa et al, 2009; Cichalewski et al, 2015; Boulet et al, 2017). Such formulations as “cough with exercise” (Langdeau et al, 2000), “cough during/after exercise” (Stelmach et al, 2016) or exercise-induced cough” (Nair et al, 2017) however do not establish whether cough occurs during or after the physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…14, 15 Cichalewski et al 16 add to the recognition of this burden, reporting the prevalence of exercise-induced symptoms and bronchospasm during physical education in the natural school environment in a study of 557 Polish school children.…”
mentioning
confidence: 99%